The myth of the serpent: from the Great Snake to the henhouse - Cosendey, Beatriz Nunes; Pezzuti, Juarez Carlos Brito (Frontiers in Amphibian and Reptile Science, 2025)
IntroductionThe relationship between humans and snakes is permeated by myths and legends, which have led to these animals being seen as malevolent beings since biblical times. As a result, their interaction tends to be negative, mainly in Occidental Cultures, often leading to the frequent killing of snakes in cases of perceived self-defense. Among them, anacondas stand out as the largest snake species in Brazil, widely known through legends such as the “Boiuna” and the “Cobra Grande.” As this is a semi-aquatic species, some traditional populations, such as the varzeiros (riverine people who live in periodically flooded áreas known as várzea), have a historical generational coexistence with these animals.MethodsHere, we focus on the várzea regions of the Lower Amazon River, where despite the lack of official studies on snake hunting, it is a known region of conflict. By analyzing different narratives from the local populations, we dug some key points behind the conflicts between humans and the local anaconda population, aiming to understand the main causes of killings and explore potential arguments to prevent them.ResultsOur findings reveal that local dwellers possess notable ecological and biological knowledge about the anaconda, particularly its feeding and reproductive behaviors. However, their perceptions of these snakes remain predominantly negative. We identified a cultural aspect in the act of killing anacondas, as men often expressed the perceived necessity to do so. Most notably, we observed that the primary trigger for these killings was anger due to economic losses, while fear acted as a deterrent to slaughter.ConclusionBased on this, our results suggest the development of a collaborative management plan and conservation strategy for anacondas, with an emphasis on protecting the local economy. Improving henhouse structures and a management plan for the use or trade of anaconda fat appear to be promising initial steps.